Meningkatkan Kemampuan Kognitif Anak Usia 4-5 Tahun Melalui Permainan Media Digital di PAUD Ibnu Abbas Kabupaten Cianjur - Supiati, Neneng (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2025)
Education provided to early childhood is education provided to optimize the growth and development of children's brains. Of course, it is necessary to have someone who is able to direct and guide children in that phase to maximize their growth. In the digital era like today, everyone is racing with technological developments, including in early childhood learning. Teachers are required to improve relevant learning innovations by utilizing relevant learning innovations by utilizing rapidly developing technology and communication. This digital media is often used as a learning and entertainment media tool.  However, the uncontrolled use of digital media risks causing various problems. The method used is classroom action research (PTK) using Mc Taggart's research design and the Kemmis model, where the data collection uses interview, observation, and documentation techniques. Qualitative descriptive data analysis techniques are to determine the improvement of the learning process, especially the various actions taken by teachers. Based on the research conducted, it can be concluded that PAUD Ibnu Abbas Cianjur Regency implements an innovation that is expected to be able to improve children's social-emotional skills (self-awareness), namely digital media introduced in the form of educational games called "Cheerful Picture Guessing Game".